Effect of LDL Extracted from Human Plasma on Membrane Stiffness in Living Endothelial Cells and Macrophages via Scanning Ion Conductance Microscopy - Diana Kiseleva; Vasilii Kolmogorov; Vadim Cherednichenko; Ulyana Khovantseva; Anastasia Bogatyreva; Yuliya Markina; Petr Gorelkin; Alexander Erofeev; Alexander Markin (Cells, 2024)
Mechanical properties of living cells play a crucial role in a wide range of biological functions and pathologies, including atherosclerosis. We used low-stress Scanning Ion-Conductance Microscopy (SICM) correlated with confocal imaging and demonstrated the topographical changes and mechanical properties alterations in EA.hy926 and THP-1 exposed to LDL extracted from CVD patients’ blood samples. We show that the cells stiffened in the presence of LDL, which also triggered caveolae formation. Endothelial cells accumulated less cholesterol in the form of lipid droplets in comparison to THP-1 cells based on fluorescence intensity data and biochemical analysis; however, the effect on Young’s modulus is higher. The cell stiffness is closely connected to the distribution of lipid droplets along the z-axis. In conclusion, we show that the sensitivity of endothelial cells to LDL is higher compared to that of THP-1, triggering changes in the cytoskeleton and membrane stiffness which may result in the increased permeability of the intima layer due to loss of intercellular connections and adhesion.